2022
DOI: 10.1016/j.japh.2021.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes outcomes before and during telehealth advancements surrounding COVID-19

Abstract: Background Pharmacists can optimize outcomes related to diabetes mellitus (T2DM) by taking advantage of telehealth opportunities despite the COVID-19 Public Health Emergency (COVID-19 PHE). Objective Identify and compare changes in T2DM outcomes prior to (August 2019 through February 2020) and during (March 2020 through October 2020) the COVID-19 PHE. Secondary objectives were to identify and compare pay-for-performance metrics and additional fee-for-service submitted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
1
7
0
Order By: Relevance
“…In contrast, decreases in measured blood pressure control may have resulted from the lack of standardized blood pressure documentation in EHRs during telehealth visits rather than poor control, although this was untestable in our data. While these findings fill an important evidence gap by focusing on Medicaid-enrolled FQHC patients, they are largely consistent with previous literature showing the potential for telehealth to improve access and some quality of care-sensitive outcomes in diabetic populations [8][9][10].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, decreases in measured blood pressure control may have resulted from the lack of standardized blood pressure documentation in EHRs during telehealth visits rather than poor control, although this was untestable in our data. While these findings fill an important evidence gap by focusing on Medicaid-enrolled FQHC patients, they are largely consistent with previous literature showing the potential for telehealth to improve access and some quality of care-sensitive outcomes in diabetic populations [8][9][10].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings support other studies that suggested that digitally supported programs were effective alternatives in mitigating some of the negative behavioral and lifestyle effects of government-enforced public health measures ( 15 , 17 ). Likewise, telehealth can be considered a practical and efficacious healthcare delivery mode for chronic diseases during the COVID-19 pandemic ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…These digitally delivered weight loss programs were effective in eliciting short-term weight loss during the pandemic ( 15 , 16 ). Furthermore, the pandemic also transformed the provision of medical care, especially in the management of various chronic diseases, by promoting the use and implementation of telemedicine ( 18 – 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that both in-person and virtual visits have similar outcomes. 32 The majority of published pharmacist models generally focus on scheduled telephone visits with interventions focused on pharmacist-led telephonic clinics, post-discharge follow-up, laboratory monitoring, and medication counseling. 33 Pharmacists have integrated technology into their visits through different means.…”
Section: Use Of Telemanagementmentioning
confidence: 99%